(STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2016) - Lorenza Aryatama, 14.05.52.0293; Jaeni, Jaeni (Students' Journal of Accounting and Banking, 2018)
This study tested the influence of profitability, financial risk, the value of the company, the structure of managerial ownership, the structure of public ownership, and the size of the company against the practice of smoothing earnings. This research was conducted in Indonesia stock exchange by using all manufacturing companyregistered and go public. The population in this research are manufacturing companieslisted on the Indonesia stock exchange (BEI) in 2013-2016. The sample was determined based on purposive samplingmethod, based on the criteria obtained by 56 companies sampled in this research. The relationship and or influence between variables is described by using the method of logistic regression analysis. This resultsshowed that of profitability, financial risk, the value of the company, and the size of the company affect againstto the practice of income smoothing. While The structure of managerial ownership, and the structure of public ownership do notaffect against the practice of income smoothing. Keyword: Income Smoothing, Profitability, Financial Risk, The value of the company, The Structure of Managerial Ownership, The Structure of Public Ownership, The size of the company